PRAKTIK PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KOTA AMBON - Dayanto Dayanto (Faculty of Law, Universitas Pattimura, 2015)
The purpose of this study was to analyze the practice of public participation in the formation of local regulation, the factors that affect, and forms of such participation. The study was conducted in the city of Ambon by using a type of juridical sociological. The results showed that the implementation of public participation in the establishment of Local Regulation in Ambon not maximized due to the lack of publication / dissemination of the legislative agenda to the public; the lack of awareness of community participation; and the rule of law on the mechanism of participation is not adequate. Participation is generally performed in the establishment of Local Regulation in Ambon is channeling aspirations through leaders / members of parliament, this shows the strength of political culture / development which is still dominated by a relationship that is patron-client.